HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN INTRA UTERINFETAL DEATH DI RSUD RADEN MATTAHER PROVINSI JAMBI - Rosa Riya (MIDWIFERY HEALTH JOURNAL, 2019)
According to the World Health Organization (WHO) and Obstetricians and gynecologists called Intra Uterine Fetal Death are fetuses that die in the womb with a body weight of 500 grams or more or the death of the fetus in the womb at pregnancy 20 weeks or more. IUFD is included in perinatal problems which is one of the health indicators, so this is very sensitive because it deals with maternal and perinatal health. IUFD is one of the causes of perinatal death (Saefudin, 2010). This study aims to determine the relationship between age and parity with Fetal Death Intra-Uterine Events in Raden Mattaher General Hospital Jambi in 2019. This study is an analytic case control study. Population of this study The population in this study was divided into two groups, namely the case group was the Fetal Death Intra-Uterine Incidence in 2018 as many as 44 people and the control group was not with the Intra Uterin Fetal Death Event in 2018. Samples were as many as 88 people were taken by total sampling technique.This research was conducted at Raden Mattaher Hospital in Jambi in May 2019. Data were analyzed by univariate and bivariate using the chi square test. The results showed that 57 respondents (64.8%) were at risk and as many as 53 respondents (60.2%) had no risk of parity. There is a relationship between age (p value = 0.002, OR = 4.929) and parity (p value = 0.191, OR = 1957) with Intra Uterine Fetal Death with p-value <0.05. There is a significant correlation between age and LBW incidence and there is no relationship between Parity and Intra-Uterine Fetal Death. The point that can be given in this study is that health workers improve services provided during pregnancy by providing counseling, counseling, and reminding mothers to detect early pregnancy complications and routine antenatal care.